Assessment of Post-operative Complications in Patients Undergoing Thyroid Surgery - Nayak, Samatha Ramanatha; Govardhanan, K; Mohammad, Nabeel (Journal of Neonatal Surgery, 2025)
Introduction-Thyroid surgeries, among the most common surgical procedures globally, present with varied complications. Methodology-In this cross-sectional, retrospective, record-based study, a total of 107 patients who underwent thyroidectomies and satisfied the inclusion criteria, were recruited using convenience sampling technique. This study was conducted. Data were collected from medical records using a researcher-created data extraction form after ethical approval from the institutional ethics committee. The data were analysed using SPSS software with a p-value of <0.05 considered to be statistically significant. Results-Of the 107 patients who underwent thyroidectomies, 92 (85.9%) reported one or more complications. Complications were most common (90.2% of patients) in the 25-34 years age group and among females (83.3%). The most common complications were dysphagia (30.84% of patients), voice change (21.50%), and respiratory obstruction (8.41%). Temporary hypocalcemia developed in 3.74% of these patients, while tracheal injury and hematoma were documented in 3.74% and 1.87%, respectively. Conclusion-The most common post-thyroidectomy complications in this group of patients were dysphagia and voice change, while hypocalcemia, tracheal injury, and hematoma were rare complications.